THE ANALYSIS OF LANGUAGE ERRORS IN THE LINGUISTIC TAXONOMY FIELD OF PHONOLOGY IN THE DRAMA SERIES "WARINTIL-RATU GIBAH COMEBACK" - Ekfindar Diliana (Acceleration: Multidisciplinary Research Journal, 2024)
In the current digital era, TV serial content has expanded from television to social media platforms such as Instagram, Facebook, and YouTube. Popular YouTube content includes comedy dramas, including one channel named "Warintil". This content presents five main characters who play various roles in humorous everyday stories. However, although the primary goal of comedy content on YouTube is to entertain, it is important for such content to use proper Bahasa Indonesia. The aim of this research is to describe language errors in the YouTube content titled "Warintil-Ratu Gibah Comeback" in the field of phonology, identify the causes of language errors, and find possible solutions. A qualitative descriptive method is used in analyzing phonological errors in the Warintil YouTube content. The results of the research show that there are language errors in the field of phonology such as phoneme deletion with a total of 4 errors, phoneme substitution with a total of 5 errors, phoneme omission with a total of 4 errors, and irregular phoneme changes with a total of 1 error.